ITE Legal Review on the Use of Computer Technology in Geological Exploration and Digital Accounting Systems - Hasan, Hamida; Alyasa-Gan, Siti Sarah; Hasan, Haslindah; Syahril, Muh. Akbar Fhad (Amsir Accounting & Finance Journal, 2024)
The development of information and communication technology has changed various aspects of human life significantly. In Indonesia, Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (UU ITE) has been promulgated to regulate the use of information technology and electronic transactions. However, along with the rapid development of technology, UU ITE has undergone two changes, the last one being through Undang-Undang Nomor 1 Tahun 2024. This study aims to explore the application of ITE law in the use of computer technology for geological exploration and digital accounting systems, using a qualitative approach with a case study design. The results of the study show that the implementation of ITE law still faces challenges related to data protection and information security. Many companies find it difficult to ensure compliance with ITE legal regulations, while sensitive geological and accounting data is vulnerable to unauthorized access and data leakage. The implications of the research are the need to increase socialization and training of ITE law, update information security policies, and adopt advanced security technologies to protect sensitive data more effectively.